Exploring sustainability from the Islamic finance perspective - Valerio, Brescia; Adam Sa'ad, Auwal; Hassan, Rusni; Syed Jaafar Alhabshi, Syed Musa; Federico, Lanzalonga (2021)
Abstract— The article explores a sample of papers on Islamic finance and sustainability to define some streams of literature on this topic. The paper aims to validate whether it is possible to interpret the multitude of contributions in three different research streams that consider environmental, economic, and social sustainability. The research conducts a structured literature review on 73 articles extracted from Scopus. Additionally, the bibliometric analysis revealed the descriptive statistics on this field and the main themes through the authors’ keywords. The different perspectives showed the multicultural nature of the topic, which is not only addressed by Islamic countries. Moreover, it made it possible to find correspondence in the theorization underlying the article and to categorize the topics covered by the authors.